The revised International Association for the Study of Pain definition of pain: concepts, challenges, and compromises - Raja, Srinivasa; Carr, Daniel B.; Cohen, Milton; Finnerup, Nanna B.; Flor, Herta; Gibson, Stephen J.; Keefe, Francis J.; Mogil, Jeffrey S.; Ringkamp, Matthias; Sluka, Kathleen A.; Song, Xue-Jun; Stevens, Bonnie; et al. (Pain, 2020)
The current International Association for the Study of Pain (IASP) definition of pain as “An unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in terms of such damage” was recommended by the Subcommittee on Taxonomy and adopted by the IASP Council in 1979. This definition has become accepted widely by health care professionals and researchers in the pain field and adopted by several professional, governmental, and nongovernmental organizations, including the World Health Organization. In recent years, some in the field have reasoned that advances in our understanding of pain warrant a reevaluation of the definition and have proposed modifications. Therefore, in 2018, the IASP formed a 14-member, multinational Presidential Task Force comprising individuals with broad expertise in clinical and basic science related to pain, to evaluate the current definition and accompanying note and recommend whether they should be retained or changed. This review provides a synopsis of the critical concepts, the analysis of comments from the IASP membership and public, and the committee's final recommendations for revisions to the definition and notes, which were discussed over a 2-year period. The task force ultimately recommended that the definition of pain be revised to “An unpleasant sensory and emotional experience associated with, or resembling that associated with, actual or potential tissue damage,” and that the accompanying notes be updated to a bulleted list that included the etymology. The revised definition and notes were unanimously accepted by the IASP Council early this year.